PENGETAHUAN DAN SIKAP REMAJA PUTRI KELAS XI TENTANG ABORSI KARENA KEHAMILAN TIDAK DIKEHENDAKI DI SMA NEGERI 1 KARANGKOBAR KABUPATEN BANJARNEGARA - Linda Yanti; Susi Wijayanti (Universitas Harapan Bangsa Purwokerto, 2010)
Background: BKKBN predict from 2,5 million abortion case per year, 1,5 million done by adolescent.based on information from school side, at SMA country 1 Karangkobar in the year teachings 2008- 2009,found 5 students that deliver out because pregnant.To detect erudition description and class daughteradolescent attitude XI about abortion because pregnancy not wish for.Methods: Watchfulness uses quantitative descriptive method with approaches cross sectional, tekhnikprimary data collecting by admission filling kuesioner where tekhnik data collecting use cluster randomsampling as big as 47 respondents. data is analyzed with analysis univariat.Results: Watchfulness shows class daughter student erudition XI SMA country 1 Karangkobar aboutabortion because pregnancy not wish for has good erudition that is as much as 26 respondents (55%) andfor attitude, a large part posed unfavorable 26 respondents (55,32%) and a part little posed favorable 21respondents (44,68%). Conclusion: Class daughter student erudition level XI SMA country 1Karangkobar about abortion because pregnancy not wish for good and student attitude unfavorable. Keyword :Erudition, attitude, adolescent daughter, abortion.